2016
DOI: 10.1038/ajg.2016.298
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled Phase 2 Study of Brodalumab in Patients With Moderate-to-Severe Crohn’s Disease

Abstract: Treatment with brodalumab resulted in a disproportionate number of cases of worsening CD in patients with active CD and no evidence of meaningful efficacy. These analyses did not suggest additional safety risks of brodalumab beyond worsening of CD symptoms in patients with active CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
214
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(233 citation statements)
references
References 20 publications
4
214
0
4
Order By: Relevance
“…These observations highlight that the presence of a cytokine in diseased tissue does not necessarily equate to an irreplaceable role in pathogenesis. Furthermore, both secukinumab20 and brodalumab21 have been demonstrated to worsen Crohn’s disease (CD). Thus, in contrast to its pro-inflammatory role in other diseases and locations, IL-17A may function as a negative regulator of immunity in the gut mucosa, perhaps via interaction with fungal elements of the intestinal microbiome 22 23.…”
Section: The Th17 Axismentioning
confidence: 99%
“…These observations highlight that the presence of a cytokine in diseased tissue does not necessarily equate to an irreplaceable role in pathogenesis. Furthermore, both secukinumab20 and brodalumab21 have been demonstrated to worsen Crohn’s disease (CD). Thus, in contrast to its pro-inflammatory role in other diseases and locations, IL-17A may function as a negative regulator of immunity in the gut mucosa, perhaps via interaction with fungal elements of the intestinal microbiome 22 23.…”
Section: The Th17 Axismentioning
confidence: 99%
“…It has been suggested that the principal function of IL-17A and IL-17RA in experimental colitis is the maintenance of intestinal barrier integrity rather than driving pathogenic inflammation. Clinical trials of anti-IL-17A (secukinumab) and anti-IL-17RA (brodalumab) Abs in patients with moderate-to-severe CD have reported no improvement, or even a worsening of disease, on treatment 97, 98 . The high levels of mRNA for T H 17 signature cytokines, including IL-17A, IL-17F, IL-22, and IL-26, in the intestinal mucosa of patients with IBD may therefore be beneficial 99102 .…”
Section: Il-17 In the Intestinementioning
confidence: 99%
“…In contrast to the benefit evident in neutralising TNF, a contributing role for IL-17 in IBD is still uncertain, and IL-12/IL-23 are likely not the driver cytokines as there is only marginal efficacy from ustekinumab (anti-12/IL-23) in CD patients, and no benefit was evident in initial trials with briakinumab (anti-IL-12/IL-23 p40-neutralising mAbs) [54]. Indeed, brodalumab (anti-IL-17RA-neutralising mAb) caused worsening symptoms in CD [55]. Clearly, further investigation into the complex interactions between the normal and altered microbiome, and the endogenous intestinal cells, including resident innate and adaptive immune cells, is required to better understand these IBD pathologies.…”
Section: Inflammatory Cytokines In Psoriasis (And Psoriatic-type Arthmentioning
confidence: 99%
“…Brodalumab, an IL-17RA-specific mAb, is one such reagent that acts by preventing IL-17-family cytokines from binding to the IL-17 receptor (Box 4). Recent Brodalumab data, derived from phase II and III clinical trials, have demonstrated effectiveness in the treatment of psoriasis [32], and reportedly with superior skin clearance than the anti-IL-12/ IL-23 mAb ustekinumab [55,82]. These are long-awaited treatment for a skin condition that has previously proven to be difficult to treat.…”
Section: Cytokine-neutralising Mabsmentioning
confidence: 99%